Measuring the deterrence properties of competition policy: the Competition Policy Indexes - Paolo Buccirossi; Lorenzo Ciari; Tomaso Duso; Giancarlo Spagnolo; Cristiana Vitale (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2009)
The aim of this paper is to describe in detail a set of newly developed indicators of the quality of competition policy, Competition Policy Indexes, or CPIs. The CPIs measure the deterrence properties of a competition policy in a jurisdiction, where for competition policy we mean the antitrust legislation, including the merger control provisions, and its enforcement. The CPIs incorporate data on how the key features of a competition policy regime score against a benchmark of generally-agreed best practices and summarise them so as to allow cross-country and cross-time comparisons. The CPIs have been calculated for a sample of 13 OECD jurisdictions over the period 1995-2005.
urn:nbn:de:bvb:19-epub-13270-9
Keywords: K21; K42; L40; 330; Competition Policy; Indicator; Deterrence; Competition Law; Wettbewerbspolitik; Kartellrecht; Fusionskontrolle; Rechtsdurchsetzung; Ankündigungseffekt; Messung; Index; OECD-Staaten